Conversion of in-process optical and thermal data into a single 3D file representing printing process in powder bed fusion - Zhang, Xuan (ASTM International, 2022)
Rapid development of additive manufacturing (AM) technologies leads to an increasing demand for quality control of printed parts. While in-process monitoring systems and post-testing technologies have been developed to inspect the part quality, there is not yet a well-established method that specifies the procedures and requirements to convert the extracted in-process layer-wise information into a single 3D file for quality evaluation and control. In this study, an off-axial imaging system utilizing optical and thermal cameras is deployed to acquire in-process optical and thermal images of the Powder Bed Fusion (PBF) process. Image registration and analyses are then performed on the acquired images to extract the in-process layer-wise data (e.g., coordinates, gray value, and temperature) associated with the printing process. Based on a comparison of file formats commonly used in industrial software, we select the Extensible Markup Language (XML) file format, which is specified by post-processing software, and further propose procedures for constructing a single 3D file from the in-process data to represent the printing process and evaluate the printing quality. This work provides guidelines for conversion of in-process data into 3D files and contributes to in-process monitoring and quality control of AM manufactured parts.